Arterial supply and morphological characteristics of sympathetic neurons in the human superior cervical ganglion - Boljanović, Jelena; Milisavljević, Milan; Latas, Milan; Puškaš, Laslo; Bogosavljević, Nikola; Vujačić, Marko; Aleksandrić, Dejan; Ćetković, Dejan; Branković, Nemanja; Dožić, Aleksandra; Ćetković, Mila (Frontiers in Neuroanatomy, 2024)
The aim of this study was the micromorphological analysis of the distribution of microvessels, mast cells and ganglionic neurons in two parts, proximal and distal of the human superior cervical sympathetic ganglions (SCSGs). Statistical analyses were applied to detect the possible metric regional differences in their densities. Five injected human SCSGs with colored India ink and gelatin were microdissected and examined. Second group of five human SCSGs was prepared and serially sliced for CD34 and mast cell tryptase immunostaining. The microscopic fields of two parts of the SCSGs were analyzed for the following quantifications: microvessel density (MVD), mast cell density (MCD), and ganglionic cell count and measurements. The mean number of CD34-positive microvessels in microscopic fields, the MVD, had a value of 83 for the upper parts, and 82.7 for the lower parts of SCSGs. The mean number of tryptase-positive mast cells in microscopic fields, the MCD, was 4.5 in the proximal parts, and 4.7 in the distal parts of SCSGs. The mean number of ganglionic neurons in microscopic fields was 19.5 in the proximal parts, and 19.8 in the distal parts of SCSGs. The density of CD34-positive microvessels, the density of tryptase-positive mast cells, and the density, mean diameters and mean areas of ganglionic neurons were not significantly different in two observed parts, upper and lower of the SCSGs. In conclusion, the distributions of microvessels, mast cells, and neurons in two parts of the SCSGs were uniform with no specific micromorphological variations, there is a homogenous vascular and cellular pattern within the SCSGs.